Voltage-mode cascadable all-pass sections with two grounded passive components and one active element - Maheshwari S.; Mohan J.; Chauhan D.S. (My University, 2025)
Two new first-order voltage-mode (VM) cascadable all-pass sections are proposed using a single, active element and two grounded passive components, ideal for IC implementation. The active element used is a fully differential current conveyor. All the circuits possess high input and low output impedances, which is a desirable feature for VM circuits. The proposed circuits are verified through PSPICE simulation results. The circuits have useful analogue signal processing applications in nth-order all-pass filter and multiphase oscillator. © 2010 © The Institution of Engineering and Technology.